Respuesta :

B

Establish the equation of the line in slope-intercept form

y = mx + c ( m is the slope and c the y-intercept )

to calculate m use the gradient formula

m = (y₂ - y₁ ) / (x₂ - x₁ )

with (x₁, y₁) = (- 3, - 3 ) and (x₂, y₂) = (3, - 1) ← 2 points on the line

m = [tex]\frac{-1+3}{3+3}[/tex] = [tex]\frac{2}{6}[/tex] = [tex]\frac{1}{3}[/tex]

the y-intercept is (0 , - 2 ) ⇒ c = - 2

y = [tex]\frac{1}{3}[/tex] x - 2 ← equation of line

This is a strict inequality since the line is broken, hence

y > [tex]\frac{1}{3}[/tex] x - 2 → B





ACCESS MORE